Shadowing correlation assessment and modeling for satellite diversity in urban environments - Vazquez-Castro, M.; Perez-Fontan, F.; Saunders, S. R. (International journal of satellite communications, 2002)
Non‐geostationary orbit satellite networks have dynamic, yet deterministic topologies. This paper deals with the consequences of relying on the use of multiple visible satellites to improve availability with time/locations through satellite diversity techniques. The assumption of independent blockage events in two different satellite‐to‐mobile links is generally not accurate and information on shadowing correlation should be taken into account in the assessment of availability.In this paper a shadowing correlation study for urban environments is presented and a model for the real environments, as well as for a generic urban environment is inferred. The model proposed here is simple and can be run on a computer. It also relates urban and constellation geometries thus allowing the identification of those cases for which satellite diversity gain should be expected. As a result of this analysis and modelling, we present empirical analytical expressions describing positive correlation coefficient as a function of satellite angular separation (azimuth and elevation). We also show that an angle exists above which correlation can be negative and satellite diversity can sensibly improve link availability. Copyright © 2002 John Wiley & Sons, Ltd.